Penyuluhan Metode Ceramah terhadap Pengetahuan Ibu tentang Asupan Sayur dan Buah Anak SD - Hapzah Hapzah; Nurbaya Nurbaya (Jurnal Kesehatan Manarang, 2021)
Several studies have suggested that applying patterns of consumption of vegetables and fruit since children will positively contribute to vegetable and fruit intake through adolescence and adulthood. Therefore, efforts to increase vegetable and fruit intake since childhood urgent. Azria and Husnah's research results (2016) show that there is an influence of counseling on behavioral changes about balanced nutrition in infants. The results of Afif and Sumarmi (2017) research also show that there is a relationship between the role of mothers as educators with consumption of fruit vegetables in children associated with the supply of vegetables and fruit at home. The purpose of this study was to determine the effect of nutrition counseling on lecture and discussion methods on mother's knowledge of vegetable and fruit intake in elementary school children in Mamuju Regency. This type of research is experimental. This research was conducted at 001 Mamuju Public Elementary School as the location of the control group and Rimuku Inpres Elementary School as the location of the intervention group. The sample was divided into two groups, the first group as an intervention group was given lecture nutrition counseling accompanied by discussion while the second group as a control group was given lecture counseling counseling without discussion of mothers of elementary school children. The number of samples were 30 control groups and 30 intervention groups so that the total sample was 60 people. The results showed that there was an influence of lecture nutrition counseling accompanied by a discussion of mother's knowledge about vegetable and fruit intake in elementary school children (p <0.05). It is expected that nutrition counseling is carried out through lecture methods accompanied by discussions to increase mothers' knowledge about vegetable and fruit intake in elementary school children.